Students’ perceptions of the role of the nonverbal dimension in intercultural communication : a mixed study in foreign language programs across various universities of Colombia (2023)
ABSTRACT: Foreign language programs tend to leave aside nonverbal communication (NVC) which could cause intercultural conflict or misunderstanding in interaction. It has been agreed that communication is multimodal (Kress, 2010; Álvarez Valencia, 2016) and that the nonverbal dimension has been absent from teacher education (Poyatos, 1994, 2002). From an intercultural perspective, a lack of awareness of NVC (gesture, proxemics, paralanguage) may lead to conflict or misunderstanding (Matsumoto et al., 2013). This study aims to establish the role of the nonverbal dimension in the comprehension of conflict or misunderstanding in intercultural communication of pre-service language teachers in Colombia. This explanatory study adopted a mixed method design and drew on data collected through a survey (n=204), and interviews with 10 pre-service teachers. The results indicate that, although the pre-service teachers report a limited presence of nonverbal elements of communication in their major, they consider this aspect important in (intercultural) communication, Besides, participants report NVC as an important aspect in order to avoid communication brakdows. The results point at the pressing need to actively integrate the nonverbal dimension at the pedagogical and curricular levels in teacher education programs in order to avoid misunderstanding or conflict.